The Utilization ofWater lettuce Silage (Pistia stratiotes) with Marine Yeast Inoculant in Feed of Selais (Ompok rhadinurus Ng) - Sitanggang, Firnando; Suharman, Indra; ', Adelina (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The research was conducted on July - August 2016. The purpose of thisstudied to determine the number of water lettuce silage flour in fish feedformulation selais (Ompok rhadinurus Ng) the effect on growth, feed efficiencyand protein retention. This study uses a completely randomized design (RAL)with one factor, 5 treatments and 3 replications. Treatments using flour of waterlettuce silage where are P0 (100% TK:0% SDK), P1 (95% TK:5% SDK), P2 (90TK:10% SDK), P3 (85% TK:15% SDK) and P4 (80% TK:20% SDK). WhichFeed protein contain 35%. The results showed that the highest treatmentscontained in P3. Use water lettuce silage flour formulated in the feed as much as15%, produces the best selais fish seed growth is digestibility is the feed 70,24 %,the feed efficiency is 18,03 %, specific growth rate is 1,81 % and protein retentionis 14,83 %.Key word : (Ompok rhadinurus Ng), Water Lettuce, Silage